Intervenção ecológica (?): uma análise de risco para os países signatários da Organização do Tratado de Cooperação Amazônica - Kilca, Marcelo de Vargas (2006)
This study discuss the possibility to extend the concept of humanitarian intervention/interference to the ecological intervention/interference by the UN (United Nations Organization) and the possible risks originated from it regarding the signatories of the Organization of the Amazon Cooperation Treaty; organization created, among other goals, to assure the sovereignty of the members over its respective Amazon territories. Concerning the international historic interest in the Amazon richness, the economic globalization process, demographic growth, increasing demand for natural resources and militarization of the environmental issues; the importance of this region in the following decades tends to boost. In this context, the research objective is to question whether the Right of Ecological Intervention might represent a stratagem which would have the purpose to legitimize the natural resources of the Amazon region, using on that behalf a speech of environmental concern and human rights defense. Divided into two parts, the research presents firstly i) the main criticisms observed in the literature of the Amazon Cooperation Treaty (ACT), especially during its elaboration phase and the terms in which these criticisms may be considered; ii) the objectives; iii) the Principles; and the iv) juridical nature of the Treaty, as well as the specific agencies responsible for its implementation. The second part discourses on v) the territorial dimensions problematic of the region from the analysis of the article XIX of the Treaty. Afterwards, it is done a report on the vi) international historic pressures on the region, making a brief overview from the sixteenth century up to the current days. From this contextualization the theme is approached vii) intervention, its applications and evolution in the UN context; and only then tracing, in a nutshell, some viii) considerations for the sovereignty topic, and presenting the conclusions. Methodologically, the study is based on a bibliographic research with books, essays, theses, official documents, laws and other texts. The research infers in an economical globalization conjuncture - with changing effects in the power relations - the militarization of the environmental subject, the elaboration of the Ecological Intervention notion - in the molds it is being designed - requires profound reflection, particularly for those who are at the periphery of the global power relations.